Combination of hydroquinone and fractional CO2 laser versus hydroquinone monotherapy in melasma treatment: A randomized, single-blinded, split-face clinical trial - Sanaz Nourmohammadi Abadchi; Farahnaz Fatemi Naeini; Elham Beheshtian (Wolters Kluwer Medknow Publications, 2019)
Background: Melasma is a chronic hyperpigmentation skin disorder mainly affecting women in the reproductive age. Available treatments for melasma do not lead to long-term satisfactory results. Aims: This study aimed to compare the efficacy of fractional CO2 laser in combination with topical therapy to topical therapy alone. Materials and Methods: Forty women with bilateral melasma were studied in this randomized single-blinded clinical trial. Each side of the face was randomly allotted to either topical hydroquinone 4% or combination of topical hydroquinone 4% and fractional CO2 laser. Patients received three sessions of laser therapy at 3-week intervals. Hydroquinone 4% application on both sides maintained for 3 months after the last laser session. The clinical improvement (darkness [D] and homogeneity [H] of hyperpigmentation) was measured by a blinded main investigator and an outcome assessor. Furthermore, improvement was assessed by physician's global assessment (PGA) and patient satisfaction (visual analog scale [VAS] score). Results: Significant reduction in D observed 3 weeks after combination therapy (P<0.001) and 6 weeks after monotherapy (P<0.001). Reduction in H became significant after 6 weeks in both groups (P<0.001). However, the two methods were not considerably different in any session (P>0.05). Furthermore, control and experiment sides were not significantly different considering VAS score and PGA (P>0.05). Conclusion: Considering the short-term outcome of laser and hydroquinone therapy, we can apply it to obtain earlier positive results. However, because of the lack of significant difference between the two methods and also the high cost of laser therapy, it seems better not to recommend fractional CO2 laser to patients as adjunctive therapy for long-term treatment of melasma.